Child care reforms and labor participation of migrant and native mothers - Tanja Fendel; Beate Jochimsen (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
As in other countries, also in Germany there has been large political effort to increase mothers' labor participation through child care provisions. However, it is an open question whether the latest child care reforms of 2013 are successful in this sense. While the introduction of a home care allowance, the so called "Betreuungsgeld", for families not using public child care for their children aged one and two years was expected to have negative effects, the introduced legal claim for public child care for children of the same age group should increase the use of public child care and therefore speed up the mothers' return to work after child birth. For the analysis we use the German socio-economic panel (GSOEP) and apply a multivariate analysis within the framework of a two-step difference-in-difference approach. Against expectations, results indicate that the reform had no negative effects on labor market participation of migrant mothers in the short run. Effects for the whole sample and for native mothers turn out to be significant positive. The government's motivation for the "Betreuungsgeld" was to compensate families for not claiming publicly supported child care (Reform part 1) and to support women to reenter the labor market quickly after having given birth (Reform part 2). In the short run the government seems to have reached both aims. – – Wie andere Länder ist auch Deutschland bemüht, die Arbeitsmarktpartizipation von Müttern durch ein erhöhtes Angebot öffentlicher Kinderbetreuung zu steigern. Ob die letzten Kinderbetreuungsreformen von 2013 in dieser Hinsicht erfolgreich sind, ist eine offene Frage. Während von dem eingeführten Betreuungsgeld für Familien, die für ihre Kinder im Alter von 1-2 Jahren keine öffentliche Kinderbetreuung nutzen, negative Effekte zu erwarten sind, sollte der seit 2013 geltende Rechtsanspruch auf öffentliche Betreuung für Kinder des gleichen Alters zu einem Anstieg der Nutzung öffentlicher Kinderbetreuung führen und somit die Rückkehr der Mütter in Beschäftigung beschleunigen. Für die Untersuchung nutzen wir das sozio-ökonomische Panel (SOEP) und führen eine multivariate Analyse im Rahmen eines zweistufigen "Difference-in-Difference-Ansatz" durch. Entgegen der Erwartungen finden wir für Mütter, die nach Deutschland migriert sind, in der kurzen Frist keine negativen Effekte der beiden Reformen auf das Arbeitsangebot. Für die gesamte Stichprobe sowie für deutsche Mütter ergeben sich signifikant positive Arbeitsmarktpartizipationseffekte für beide Reformteile zusammen. Ziele der Bundesregierung waren es, Familien dafür zu kompensieren keine öffentliche Kinderbetreuung für ihre jungen Kinder zu nutzen (1. Reformteil) sowie Mütter bei der Rückkehr in den Arbeitsmarkt nach der Geburt des Kindes zu unterstützen (2. Reformteil). In der kurzen Frist scheinen beide Ziele erfüllt worden zu sein.
Keywords: J13; J22; H31; 330; migration; Germany; mothers' labor supply; child care; family policy